Optical And Microwave Technologies Select Proceedings of ICNETS2, Volume IV - Gnanagurunathan, Gnanam; Sangeetha, R.G.; Kiran, K. Usha.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book gathers a collection of papers by international experts presented at the International Conference on NextGen Electronic Technologies (ICNETS2-2016). ICNETS2 encompasses six symposia covering all aspects of the electronics and communications domains, including relevant nano/micro materials and devices. Highlighting the latest research on Optical And Microwave Technologies, the book will benefit all researchers, professionals, and students working in the core areas of electronics and their applications, especially in signal processing, embedded systems, and networking.
Enhanced  Hierarchical Cluster Based Routing Protocol with Optical Sphere in FSO Manet -- Performance Improvement of Fractal Antenna with Electromagnetic Band Gap (EBG) and Defected Ground Structure for Wireless Communication -- Miniaturized Low Profile Antenna and Meta-Material Loaded Phase Shifter for Radar Application -- A Modified L-Slot Microstrip Antenna with Chamfered Patch Edges for UWB Applications -- Performance Analysis of CSRZ-DQPSK Modulator for ROF-PON Based Wireless Access -- Effects of Cross Phase Modulation and Four Wave Mixing in DWDM Optical Systems using  RZ and NRZ Signal -- Implantable Antenna for Blood Glucose Monitoring -- Reliability Analysis of Data Center Network -- Study of Microstrip Antenna Array with EBG Structure -- Gain Enhancement of Compact Multiband Antenna with Metamaterial Superstrate -- Cooperative Communication for Resource Sharing in Cognitive Radio Networks -- Interdomain Traffic Engineering with BGP and MPLS VPN -- Analysis and Critical Parameter Extraction of An Led for Brain Implants -- Review of Thermal Management of An Led for Brain Implants -- Bandgap Analysis in Defectless Photonic Crystals -- Multi Band High Gain Antenna with Cpw Feed for Wi-Fi, Wi-Max and X Band Application -- Design & Parameter Extraction of Split Ring Resonator for Surface Crack Detection in Different Materials -- Optical Channel Analysis of Turbo Coded MIMO-OFDM System for Visible Light Communication -- Frequency Tuning Method for Small Profile Metamaterial Based on Tri-Ring Resonator -- Redesigning Mach-Zehnder Modulator with Ring Resonators -- Study on Gain Enhancement of The Antenna using Planar Small Metasurface Lens -- Design of An internal Multi Resonant Pifa Antenna for Mobile  Telecommunication Networks -- Design of Substrate integrated Waveguide Back to Back Π-Shaped Slot Antenna for 60ghz Applications -- Performance Improvement of Gain in Distributed Raman Amplifier using forward and Backward Pumps -- A Comparative Study on Asymmetric, Triangular and Rectangular Core Large-Mode-Area PCF Designs -- Miniaturized High Gain Uwb Monopole Antenna with Dual Band Rejection using CSRR -- Evaluation of Environmental Factors in Bi-Directional Wdm Optical Wireless Communication in 1.55 Μm Band -- Soa Parameters Optimization for High Data Rate Operation -- All Optical 3R Regenerator of Design and Simulation -- Analysis of Dispersion Compensation Methods in WDM Systems -- Wideband Antenna for Medical Application -- Mitigation of Cross Phase Modulation in Multiband Radio-Over-Fiber Systems -- The Design of High Gain Substrate integrated Waveguide Antennas with FR4 and Rt Duroid.
Keywords: Telecommunication; Lasers; Microwaves, RF Engineering and Optical Communications; Communications Engineering, Networks; Laser